The culture and territory of polish immigration in Áurea, Rio Grande do Sul - Brazil - Socoloski, Thaimon da Silva; Cardoso, Eduardo Schiavone (Sociedade & Natureza, 2020)
The European immigration to the south of Brazil became one of the main migratory flows in the colonization process as well as in the agricultural development aimed by the Brazilian state. Considering this migratory flow, the Polish immigration was important to Rio Grande do Sul and, primarily, as the main focus in this study, the colonization of Áurea, starting in 1911. The main purpose is to discuss the importance of this migratory process to the cultural elements which appear in the routine of these Polish descendants who currently live in Áurea. Then, the following cultural codes were analyzed: religion, language and dialect, arts, dance, music, cuisine, architecture and costume. It was possible to observe that for decades and since the new generations, after more than one century of colonization, most of these codes are still alive in the traditions and the descendants’ daily habits, their religious ceremonies, the dialect and the cuisine. However, the process of new culture assimilation in Brazil has become more latent and it is replacing the tradition which survived and has been surviving among the generations closer to the immigrants. Finally, the valorization and the perpetuation of the immigrants’ heritage and memories have been kept, from generation to generation, and this process is crucial to avoid neither losing nor forgetting the history of Áurea.